THE EFFECT OF SPATIAL ASPECT ON SHOPPING AREA LAND VALUES (A Case study of Shopping Area in Bandung City Territory) - Widya Winarno (NIM 25105025), Heru
ABSTRACT: The presences of shopping area will indirectly provide a sufficient potential revenue for government. One of potential income from this typical property is Land and Building Tax. Taxation base is the selling value of tax object (NJOP). Therefore, NJOP calculation through a tax object valuation is a very vital activity in Land and Building Tax management. In considering to importance of such NJOP, thus it is required for a proper method and valuation in its implementation, so it can be produced an accurate land value information. This research has purpose to analyze the effect of spatial aspect on shopping area land values. Variables in study include distance to nearest central business district, distance to nearest public transportation station, distance to nearest housing area, nearness with other shopping area, size of building, floor area ratio, width of road, two-ways road, and appropriateness of land allocation with regional layout planning. Data analysis use multiple regression analysis with ordinary least square (OLS) method. The regression model used consists of linear (lin-lin), semilog (lin-log), semilog (log-lin) and logarithm (log-log) models. The applied model testing are economical apriory test, statistical criterion test, classical assumptions test, model evaluation and validation.